PID tuned artificial immune system hover control for lab-scaled helicopter system - Toha, Siti Fauziah; Abdul Rahim, Amir Fuhairah; Mansor, Hasmah; Akmeliawati, Rini (IEEE, 2015)
Helicopter has significant attributes as compared to its aircraft counterparts due to its capability to hover around smaller space. This advantage is very useful during air-sea mission, surveillance and disaster monitoring. However, it comes with a price where the system exhibits not only increased in sensitivity to control inputs and disturbances but also a much higher dynamics. A pitch angle control and vibration stability of such system is of prime importance. Therefore this paper presents a PID tuned AIS optimization hover control for a labscaled helicopter. The meta-heuristic ability of the artificial immune system (AIS) is used in search for optimized value of PID gain parameters as opposed to using heuristic method for conventional PID controller. It is shown in the result that the optimized control strategy has achieved a good performance and tracking response within less than 40 iterations. With a good control system response, it is anticipated the system vibration due to pitch movement will also be reduced.